Here is a "sugared" lambda expression that uses let declarations:
Let compose = λf. λg. λx. f (g x) in let h = λx. x + x in
compose h h 3
The "desugared" lambda expression, obtained when each let z = U in V is re- placed with (λz. V) U is
(λcompose.
(λh. compose h h 3) λx. x + x)
λf. λg. λx. f (g x).
This is written with the same variable names as those of the let form to make it easier to read the expression.
Simplify the desugared lambda expression by using reduction. Write one or two sentences explaining why the simpli?ed expression is the answer you expected.